2018
DOI: 10.1001/jamasurg.2018.3102
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates After Repair of Inguinal Hernia in Women

Abstract: ach year, more than 20 million procedures to repair inguinal hernia are performed worldwide. 1 The lifetime risk of developing an inguinal hernia is 27% for men compared with only 3% for women. 2 However, studies have reported that 8% to 16% of patients with inguinal hernia are females. 3,4 Nevertheless, to our knowledge, no randomized controlled trial (RCT) or systematic review has specifically addressed repair of groin hernia in women. 5 Guidelines for repair of inguinal hernias in women are based mainly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Four of our female patients were subjected to previous inguinal herniorrhaphies in other institutions. Although some authors have suggested that prior inguinal hernia repair might be a risk factor for femoral hernia development, most believe that this association is inaccurate 29 . The occurrence of femoral hernia after inguinal herniorrhaphy is possibly due to unrecognized femoral hernia during the first operation and not a new hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of our female patients were subjected to previous inguinal herniorrhaphies in other institutions. Although some authors have suggested that prior inguinal hernia repair might be a risk factor for femoral hernia development, most believe that this association is inaccurate 29 . The occurrence of femoral hernia after inguinal herniorrhaphy is possibly due to unrecognized femoral hernia during the first operation and not a new hernia.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of recurrence after inguinal hernia repair in females, Schmidt et al 29 reported that 203 of 496 patients (40.9%) with recurrent hernia had femoral hernia after open procedure compared with no recurrence after laparoscopic repair. These findings suggested that the high development of femoral hernia after inguinal herniorrhaphy was due to non-identification of femoral hernia in the initial operation because of its deep location and small size.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to date, there are no comparable findings for these data in the literature. Only the proportion of re-recurrences of around 8% is also seen in the Danish Hernia Database [ 11 ]. The data impressively demonstrate just how demanding is inguinal hernia surgery for recurrences and re-recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In recent administrative data and registry analyses it was revealed that the proportion of recurrent repairs in the total collective of inguinal hernia repairs among men was 11.3–14.3% [ 3 7 ] and in women 7.0–7.4% [ 4 , 8 ]. By contrast, in systematic reviews and meta-analyses the recurrence rates were still far lower (1.2–3%) than those cited above since the included studies had a maximum follow-up time of 6 years [ 9 11 ].…”
Section: Introductionmentioning
confidence: 91%
“…Primary hernias may be congenital or acquired (811). Unlike cancers, hernias are benign conditions and cure without recurrence is possible in almost 95% of cases, especially for groin hernias (12, 13), although the recurrence rates are higher for ventral hernias (1416). Morbidity is also very low and the mortality rate is almost zero after hernia repairs except for emergency repairs, especially in the elderly (1720).…”
Section: Introductionmentioning
confidence: 99%